Pulsed laser assisted high-throughput intracellular delivery in hanging drop based three dimensional cancer spheroids. Issue 15 (9th July 2021) - Gupta, Pallavi; Kar, Srabani; Kumar, Ashish; Tseng, Fan-Gang; Pradhan, Shantanu; Mahapatra, Pallab Sinha; Santra, Tuhin Subhra
Abstract : This is the first study to report laser mediated optoporation-based intracellular delivery in 3D cellular constructs grown in hanging drop cultures. Abstract : Targeted intracellular delivery of biomolecules and therapeutic cargo enables the controlled manipulation of cellular processes. Laser-based optoporation has emerged as a versatile, non-invasive technique that employs light-based transient physical disruption of the cell membrane and achieves high transfection efficiency with low cell damage. Testing of the delivery efficiency of optoporation-based techniques has been conducted on single cells in monolayers, but its applicability in three-dimensional (3D) cell clusters/spheroids has not been explored. Cancer cells grown as 3D tumor spheroids are widely used in anti-cancer drug screening and can be potentially employed for testing delivery efficiency. Towards this goal, we demonstrated the optoporation-based high-throughput intracellular delivery of a model fluorescent cargo (propidium iodide, PI) within 3D SiHa human cervical cancer spheroids. To enable this technique, nano-spiked core–shell gold-coated polystyrene nanoparticles (ns-AuNPs) with a high surface-to-volume ratio were fabricated. ns-AuNPs exhibited high electric field enhancement and highly localized heating at an excitation wavelength of 680 nm. ns-AuNPs were co-incubated with cancer cells within hanging droplets to enable the rapid aggregation and assembly of spheroids. Nanosecond pulsed-laser excitation at the optimized values of laser fluence (45 mJ cm −2 ), pulse frequency (10 Hz), laser exposure time (30 s), and ns-AuNP concentration (5 × 10 10 particles per ml) resulted in the successful delivery of PI dye into cancer cells. This technique ensured high delivery efficiency (89.6 ± 2.8%) while maintaining high cellular viability (97.4 ± 0.4%), thereby validating the applicability of this technique for intracellular delivery. The optoporation-based strategy can enable high-throughput single cell manipulation, is scalable towards larger 3D tissue constructs, and may provide translational benefits for the delivery of anti-cancer therapeutics to tumors.